Determinants of Intrinsic Motivation in Private School Teachers in South Kalimantan: an Empirical Analysis Based on Herzberg's Motivator Factor Theory - Rosnah Binti Ishak; Mahaliza binti Mansor; Iwan Perdana (Jurnal Syntax Transformation, 2023)
An individual or organization is guided to attain their objectives by motivation. The school's goals will be achieved if the teacher is motivated and dedicated to his duties and obligations. Based on Herzberg's theory, the purpose of this study is to identify the component that, when it comes to intrinsic motivation, has the most significant percentage among private teachers in South Kalimantan Province: achievement-quality performance, Advancement, and growth-new learning, recognition for achievement, Responsibility, and work itself. The design chosen to conduct this research is a survey. The total sample selected is 335 private school teachers. All items in the questionnaire used a five-point Likert scale to evaluate the response sample in this study. Respondents are asked to assess each item by selecting one of the five options available, ranging from 'Strongly disagree' to 'Strongly agree.' Based on the results of a study of 355 private teachers in South Kalimantan Province, it was found that their level of intrinsic motivation was generally high to very high on various aspects of the assessment. It indicates that these teachers have strong internal enthusiasm for their teaching profession.